Experimental College Student Worksheet-based on Critical Thinking Skills Training for Genetics and Evolution Course - Darmawati, Darmawati (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
The study of genetics and evolution emphasizes the problem solving and processes that require critical thinking skills. For this reason, a college student experimental worksheet (CSEW) based on critical thinking skills is needed, so that students can be more active and have a meaningful learning experience. The purpose of this research is to develop the CSEW based on critical thinking skills which will be used at the Course Genetics and Evolution. This research was conducted at the Biology Education Campus, Faculty of Teacher Training and Education (FTTE), Universitas Riau. The research starts in the odd semester 2020-2021 from September 2020 to January 2021. The process of development referred to the ADDIE model. The results showed that the overall validation of the CSEW is 3.52 or very valid categories and based on the limited scale trials is 3.50 or very good categories. While the average student critical thinking is 79.00 or in a good category. Thus, it can be concluded that the CSEW is possible to be applied in genetics and evolution courses.